Online condition monitoring and fault diagnosis in wind turbines: A comprehensive review on structure, failures, health monitoring techniques, and signal processing methods - Eyad Al Lahham; Laith Kanaan; Zaid Murad; Haris M. Khalid; Ghulam Amjad Hussain; S.M. Muyeen (Green Technologies and Sustainability)
Wind energy systems have been flourishing on a rapid scale as a reliable renewable energy source in several countries. However, as the demand for these systems continues to grow, it becomes crucial to have a reliable and cost-effective condition monitoring system to enhance their availability. Condition monitoring plays a crucial role in achieving economic and reliable wind turbine operation. Recently, online monitoring and fault detection have been gaining greater interest in protecting these systems. Innovative and novel methods are developed to achieve real-time and remote monitoring of wind turbines. Online monitoring can offer real-time data to indicate the health condition of these systems while in service. This reduces (1) loss of production and downtime, and (2) maintenance and operational costs incurred due to system failures. This proposed work presents a comprehensive review of wind turbine online condition monitoring methods and techniques presented in the literature. Moreover, the (1) structure, (2) failures, and (3) signal processing methods of wind turbine systems were presented. Furthermore, a brief comparison was presented of (1) online monitoring techniques, and (2) signal processing methods utilized for wind turbine systems. A detailed list of published work to date has been gathered to portray a complete picture of addressed developments in this area.